Management information systems - Sousa, Kenneth J.; Oz, Effy (Australia : Course Technology Cengage Learning, 2015)
This edition retains the five parts structure and updated part-opening business cases from previous editions, but features a new streamlined chapter organization to better fit your course needs.
Part I: THE INFORMATION AGE.1. Business Information Systems: An Overview.2. Strategic Uses of Information Systems.3. Business Functions and Supply Chains -- Part II: INFORMATION TECHNOLOGY.4. Business Hardware.5. Business Software.6. Business Networks and Telecommunications.7. Databases and Data Warehouses -- Part III: WEB-ENABLED COMMERCE.8. The Web-enabled Enterprise.9. Challenges of Global Information Systems -- Part IV: DECISION SUPPORT AND BUSINESS INTELLIGENCE.10. Decision Support and Expert Systems.11. Business Intelligence and Knowledge Management --.Part V: PLANNING, ACQUISITION, AND CONTROLS.12. Systems Planning and Development.13. Choices in Systems Acquisitions.14. Risks, Security, and Disaster Recovery.
Includes bibliographical references and index.
Keywords: MANAGEMENT INFORMATION SYSTEM